A model of psychological well-being among international students*. Issue 1 (2nd January 2018) - Shafaei, Azadeh; Nejati, Mehran; Abd Razak, Nordin
Abstract: This study aims to investigate the relationship between acculturation attitude (i.e. adjustment and attachment attitudes) and individuals' psychological adaptation (i.e. life satisfaction, depression and self-esteem). Additionally, the relationship between the dimensions of psychological adaptation with psychological well-being and their mediation effect are examined. Data were collected from 974 randomly selected international students pursuing their Master or Doctoral level studies in six Malaysian public universities using a structured questionnaire. Partial Least Squares Structural Equation Modelling (PLS-SEM) technique was applied to examine the relationships in the research model. The results revealed that both adjustment and attachment attitudes are significantly related to life satisfaction and self-esteem while only adjustment attitude associates with depression. All the three dimensions of psychological adaptation are significantly related to psychological well-being. Moreover, the mediation effect of life satisfaction, self-esteem and depression are supported for the relationship between adjustment attitude and psychological well-being. Study implications and contributions are presented.